“Britain Now Your Voices Join”: The Legacy of Peterloo in Song - Morgan, Alison; Coe, Peter; Peters, Brian; Smyth, Laura (Romanticism on the Net)

(untitled) (Université de Montréal, 2020)
Whilst the study of song is beginning to appear in work within the field of Romanticism, its performative nature is still largely unchartered territory, in large part due to the challenges in recovering information on the authors, singers and reception of these songs. Published as ephemeral broadsides, songsters, chapbooks or in radical journals, these songs occupy the hinterland between oral and print culture. Through the Road to Peterloo project, in which three renowned musicians from the North West recorded and performed a selection of songs published in the immediate aftermath of the massacre, the rightful return to orality of these songs requires reconsideration. Three Peterloo songs are considered in this essay, both in text and performance: the anonymous broadside ballad, “A New Song on Peterloo Meeting,” “Saint Ethelstone’s Day” by the Spencean poet, Allan Davenport, and “Peterloo” by the little-known cotton spinner-poet, John Stafford. Through an examination of these three songs and the contexts in which they were written and performed alongside the significance of the stated tunes, this essay seeks to highlight the significance of song to the wider study of the radical culture of the Romantic period and contribute to the scholarship on Peterloo. Moreover, the songs’ transformation by Coe, Peters and Smyth, which simultaneously pays tribute to the originals whilst enhancing their meaning admirably through their understanding of how these songs can connect with audiences, illustrates that it is only through the mediation of performance that these texts truly come alive.